2021
DOI: 10.3390/ijms222313060
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Bases of Human Malformation Syndromes Involving the SHH Pathway: GLIA/R Balance and Cardinal Phenotypes

Abstract: Human hereditary malformation syndromes are caused by mutations in the genes of the signal transduction molecules involved in fetal development. Among them, the Sonic hedgehog (SHH) signaling pathway is the most important, and many syndromes result from its disruption. In this review, we summarize the molecular mechanisms and role in embryonic morphogenesis of the SHH pathway, then classify the phenotype of each malformation syndrome associated with mutations of major molecules in the pathway. The output of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…Conditional knockout of Kif3a, resulting in expansion of the Hedgehog responsiveness of the face, has been shown to lead to hypertelorism (Brugmann et al, 2010). In view of such mice experiments, gain‐of‐function mutation in human SHH would lead to excessive expansion of the facial midline or the hypertelorism phenotype (Abramyan, 2019; Dworkin et al, 2016; Niida et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Conditional knockout of Kif3a, resulting in expansion of the Hedgehog responsiveness of the face, has been shown to lead to hypertelorism (Brugmann et al, 2010). In view of such mice experiments, gain‐of‐function mutation in human SHH would lead to excessive expansion of the facial midline or the hypertelorism phenotype (Abramyan, 2019; Dworkin et al, 2016; Niida et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Freed of PTCH1-mediated suppression, SMO relieves the sequestration by SUFU and phosphorylation from PKA, CK1, and GSK3β, thus stabilizing the GLI proteins in their full-length transcriptional activator form. The activated GLI (GLIa) translocates into the nucleus and promotes the transcription of SHH target genes ( Figure 1B ) ( Briscoe and Thérond, 2013 ; Niida et al, 2021 ; Sigafoos et al, 2021 ). Here, we observed that the SHH signaling pathway is a highly regulated cascade of extracellular ligands, receptor proteins, cytoplasmic signaling molecules, transcription factors, coregulators, and target genes.…”
Section: Introductionmentioning
confidence: 99%